Grupos Económicos Centroamericanos y Cambio climático: Entre las (RE)- Autoregulaciones y la competitividad en una región de alta vulnerabilidad - López R., Alexander (2014)
According to the United Nations FrameworkConvention on Climate Change,this phenomenon is defined aschanges to the global climate system directlyor indirectly attributable to humanactivity that interact with natural climatevariability as observed during comparabletime periods. In Central Americathe increased occurrence and intensityof drought, flooding, forest fires and hurricanesas a result of global warminghave caused astronomical losses insectors like agriculture and tourism. Inthis context, the present article attemptsto respond to the following questions:Why is climate change important to theagendas of economic groups? How doesa climate change impact the economy?How have Central American economicgroups responded to increased vulnerabilityto the effects of climate changeat the national and regional levels?And finally, what best practices has theregion´s business sector developed toconfront the process of climate change?